2013
DOI: 10.1088/0953-8984/25/42/425302
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric polarization, anisotropy and nonradiative energy transfer into nanometre-scale thin semiconducting films

Abstract: A common problem of nonradiative energy transfer (NRET) from a small energy donor into a neighbouring energy acceptor layer is addressed with the emphasis on the layer thickness dependence. Two complementary approaches are employed to study dielectric polarization effects on NRET into thin films: a macroscopic analysis treating the acceptor layer as a continuum characterized by a frequency-dependent dielectric function, and a direct modelling utilizing discrete acceptor lattices, each of the acceptors being a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Prins et al examined the ET between CdSe QDs and MoS 2 of different thicknesses. 201 Similar to the graphene-QD system, the ET rate from QDs to the 2D semiconductor MoS 2 can be also modulated through the The device gives a PL modulation efficiency of 75% and the authors believe the method can be extended to other QD/2D semiconductor combinations. 16).…”
Section: Et Involving 2d Materialsmentioning
confidence: 99%
“…Prins et al examined the ET between CdSe QDs and MoS 2 of different thicknesses. 201 Similar to the graphene-QD system, the ET rate from QDs to the 2D semiconductor MoS 2 can be also modulated through the The device gives a PL modulation efficiency of 75% and the authors believe the method can be extended to other QD/2D semiconductor combinations. 16).…”
Section: Et Involving 2d Materialsmentioning
confidence: 99%
“…On the other hand, materials such as MoS 2 , WS 2 , and InAs will show FRET that becomes weaker as the layer thickness is increased . Furthermore, Gartstein et al theoretically investigated and compared both macroscopic analyses by considering an acceptor slab having a complex dielectric function (i.e., CPS theory) and direct modeling, which considered discrete acceptor layers as polarizable point dipoles . In both models, non‐additivity (non‐monotonic behavior) in FRET efficiencies is observed as a function of the acceptor layer thickness, especially when the polarizability of the acceptor layer is relatively high (e.g., ε ′ > 7 and ε ″ = 0.2).…”
Section: Two‐dimensional Materials As Efficient Exciton Sinksmentioning
confidence: 99%
“…The authors of ref. [30] use a bulk dielectric permittivity to describe the optical response of the MoS 2 and they attribute the decreasing behavior to dielectric screening [45]. In particular, they found that, by increasing the thickness of the MoS 2 slab, the field intensity created by a dipole source on the slab drops.…”
Section: B Spontaneous Emission In the Presence Of A Single Mos 2 Layermentioning
confidence: 99%